1991
DOI: 10.1016/0014-5793(91)80159-z
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol‐ester‐induced phosphorylation of the β2‐adrenergic receptor decreases its coupling to Gs

Abstract: Phorb~l.e~ter~ hawe been ~thown to modulate the//.adr©ner|i¢.~timulated adenylyl c)'cla~ in n number el'cell line~. Here, us[nit ~ila directed muta.genesis, we invesligate the role of the #~.adrencrgic receptor phosphorylation by protein kin~se C in thi,~ regulatory process Mulation of the serinc.281, -~$2, -144 ,rid -345 el" the//.,.adren~rili¢ r¢c¢ ptor prevented the phorhol.ester-induced phosphorylation of Ihe receptor. This nBll~lIOn also ;tholi*hed the phorbol.o~ter.induccd decrease in high.dignity ~lloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 34 publications
4
25
0
Order By: Relevance
“…Previous studies have shown that PKA desensitization of the ␤ 2 AR was heterologous; that is, that any stimulation of cAMP and PKA could lead to a desensitization of epinephrine stimulation of adenylyl cyclase. We and others have also shown that activation of PKC with PMA led to a similar desensitization in a number of cell types (Clark et al, 1988Kunkel et al, 1989;Johnson et al, 1990;Bouvier et al, 1991;Hausdorff et al, 1991;Yuan et al, 1994). Both the PKA-and PKC-mediated desensitizations were shown to be ablated with an S261,262A substitution mutant of the ␤ 2 AR (Johnson et al, 1990;Yuan et al, 1994).…”
Section: Resultssupporting
confidence: 53%
“…Previous studies have shown that PKA desensitization of the ␤ 2 AR was heterologous; that is, that any stimulation of cAMP and PKA could lead to a desensitization of epinephrine stimulation of adenylyl cyclase. We and others have also shown that activation of PKC with PMA led to a similar desensitization in a number of cell types (Clark et al, 1988Kunkel et al, 1989;Johnson et al, 1990;Bouvier et al, 1991;Hausdorff et al, 1991;Yuan et al, 1994). Both the PKA-and PKC-mediated desensitizations were shown to be ablated with an S261,262A substitution mutant of the ␤ 2 AR (Johnson et al, 1990;Yuan et al, 1994).…”
Section: Resultssupporting
confidence: 53%
“…A potential explanation for this apparent paradox could be that the increased basal cAMP production, resulting from the cholesterol depletion, leads to PKA-mediated receptor desensitization and attenuates ␤ 2 AR/G s coupling. Consistent with this notion, PKA-dependent phosphorylation of the ␤ 2 AR has been shown previously to promote receptor uncoupling (30,45,46).…”
Section: Membrane Cholesterol Regulatessupporting
confidence: 63%
“…HA-␤ 2 AR WT was described previously (29). cDNA of ␤ 2 AR PKAϪ , as described (30), was subcloned into pcDNA3.1 following HindIII/EcoRI digestion. ␤ 2 AR-Luc was described previously (31).…”
Section: Methodsmentioning
confidence: 99%
“…For the ␣ 1 AR, PMA pretreatment results in phosphorylation of the receptor and decreased coupling to phosphoinositide hydrolysis . ␤ 2 AR function has also been shown to be decreased by phorbol esters, an effect associated with receptor phosphorylation (Bouvier et al 1991). One of the most well characterized G protein-coupled receptor signaling pathways that is altered by PKC-mediated receptor phosphorylation is that of the 5HT 1A receptor (Raymond, 1991), where the sites of this phosphorylation recently have been mapped (Lembo and Albert, 1995).…”
Section: Resultsmentioning
confidence: 99%